2021
DOI: 10.1371/journal.pone.0253387
|View full text |Cite
|
Sign up to set email alerts
|

Classification of cannabis strains in the Canadian market with discriminant analysis of principal components using genome-wide single nucleotide polymorphisms

Abstract: The cannabis community typically uses the terms “Sativa” and “Indica” to characterize drug strains with high tetrahydrocannabinol (THC) levels. Due to large scale, extensive, and unrecorded hybridization in the past 40 years, this vernacular naming convention has become unreliable and inadequate for identifying or selecting strains for clinical research and medicinal production. Additionally, cannabidiol (CBD) dominant strains and balanced strains (or intermediate strains, which have intermediate levels of THC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…There were many offers of blend or hybrid options available in every product category. The taxonomical classification of cannabis into indica and sativa are mostly based on marketing considerations as they do not exist in nature due to historical cross-breeding and misuse of nomenclature ( 50 , 51 ). However, cannabis users report differential subjective experiences between indica- and sativa-dominant products with greater preference for using indica in the evening while reporting feeling “relaxed, sleepy/tired” and sativa during the day while reporting feeling “alert/energized” ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…There were many offers of blend or hybrid options available in every product category. The taxonomical classification of cannabis into indica and sativa are mostly based on marketing considerations as they do not exist in nature due to historical cross-breeding and misuse of nomenclature ( 50 , 51 ). However, cannabis users report differential subjective experiences between indica- and sativa-dominant products with greater preference for using indica in the evening while reporting feeling “relaxed, sleepy/tired” and sativa during the day while reporting feeling “alert/energized” ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the same study also concluded that neither the name associated with a sample nor its reported ancestry was a reliable predictor of its genetic identity (Sawler et al, 2015). Two very recent large-scale SNP analyses confirmed that the vernacular label of Sativa and Indica could only poorly account for the overall genetic relatedness of different cultivars (Jin et al, 2021; Watts et al, 2021). While this is frustrating from a scientific perspective, recent data highlight the importance of using cannabis formulations in scientific experiments which match those on the market; although again little genetic justification for the labeling of cultivars as Indica, Sativa, or hybrid was observed, the “research-grade cannabis” supplied by the National Institute on Drug Abuse was genetically distinct from those available from retail dispensaries (Schwabe et al, 2021), making its utility in scientific investigations questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has used various reference genomes [18] [24] [31] [68] and this reflects the current predicament within the industry where standards are still in development. The cs10 reference genome is the most complete assembly to date, but it contains non-functional THCAS gene sequences.…”
Section: Discussionmentioning
confidence: 99%